Pharmacological evaluation of oxazine sulfonamide derivatives for anti-inflammatory, analgesic and antipyretic activities - Ande, Shailaja; Shaik, khadar; Dharmoji, Ravi; Firdouse, Nisa; Mohd, Anjum; Yelwarthi, Sowmya (International Journal of Pharmacology and Toxicology, 2016)
Oxazine heterocyclic compound containing one oxygen and one nitrogen atom. They possess different pharmacological activities like anticancer, anti-ulcer, antifungal, antithrombotic, antihypertensive, analgesic, anti-inflammatory etc. Oxazine Sulphonamide derivatives were investigated for anti-inflammatory, analgesic and anti-pyretic activities. It was evaluated for anti-inflammatory activity by carrageenan induced paw edema in rats using Plethysmometer and it also shows significant analgesic effect in male Albino mice. Antipyretic activity was also investigated.